Dos pressupostos conceituais sobre competência à concepção de competência na metodologia do SENAI - Santos, José Antônio Oliveira dos (2014)
This study has theoretical connections and focuses on the conceptions about competence in the vision of authors who talk about such a concept and how they are approaching or distancing themselves from the conception about competence present in the guide devices of the Methodology by Competence proposed by the National Service for Industrial Apprenticeship (SENAI). The development of competences constitutes one of the guiding axes of Professional Education, whose centrality is emphasized in the legal provisions that guide this teaching modality. We used the documentary analysis of legal provisions that concern Professional Education and also of the SENAI´s guiding documents (Elaboration of Professional Profiles by Segment Technical Committees; Elaboration of Curricular Design and Guide of the Pedagogical Practice). In order to analyze the conceptions about competence we used the following authors: Berger (1999), Rios (1999), Perrenoud (1999), Le Boterf (2003), Depresbiteris (2005), Sacristan (2011), Macarenco (2011). Data were analyzed by the Content Analysis Technique proposed by Bardin (2009) and categorized into two thematic axes: a) Approaches between concepts of competence; and b) Distances between concepts of competence. Through this study we could: a) comprehend the different concepts about competence of these authors; b) confront the concepts of these authors with SENAI's concept of competence; c) identify the approaches and the distances between the researched concepts; and d) submit a proposal to revitalize SENAI's concept of competence. We long for the reflections arising from the findings of the research will contribute to revitalize the understanding of competence and to expand the competence concept in the SENAI Methodology for Training by Competence guiding devices.